Implementasi Kebijakan Kepemimpinan dalam Pengembangan Pendidikan Non Formal di Pondok Pesantren Al-Baqiyatussa’adiyah Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir - Muhammadiyah Muhammadiyah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2020)
This study aims to find out 1) To find out the leadership policies in preparing the agenda for developing non-formal education at the al-Baqiyatussa'adiah Islamic boarding school, Tembilahan Hulu District, Indragiri Hilir Regency, 2) To find out the leadership policies in implementing the development of non-formal education in the al-Islamic boarding school. Baqiyatussa'adiah, Tembilahan Hulu District, Indragiri Hilir Regency. This research uses the type of field (field research) with a naturalistic qualitative approach. Data collection techniques with in-depth interviews, observation and documentation. The results of the study conclude that: Policies in the development of non-formal education development agendas begin with environmental observations, input from institutional leaders and the kiai's own initiative. The main issues will first be discussed within the scope of the institution, then forwarded in a large meeting or directly to the chairman of the foundation and caregivers. This is what makes the development of non-formal education at the Al-Baqiyatussa'adiah Islamic Boarding School different from other Islamic boarding schools. Meanwhile, the formulation of policy problems was obtained through many sources including input from education administrators, committee administrators, foundation administrators. Policy implementation in the development of non-formal education is through the realization of the vision and mission of the foundation. The development of non-formal education involves the administrators of related institutions according to their respective policy areas, fully facilitates the needs of students for non-academic activities, for infrastructure needs to communicate with the guardians of students and non-permanent donors, fully facilitates extracurricular activities.